Cocoa, custom, and socio-economic change in rural Western Nigeria - Berry, Sara S. (Oxford : Clarendon Press, 1975)
In this study, the author examines the development of cocoa farming in Western Nigeria since the late nineteenth century as a process of capital formation in a land surplus economy.
Includes index.
Includes bibliographical references: p. 225-233.
ne 17/10/2019
Loans
Keywords: Cocoa trade; Nigeria, Western